Pelatihan Pembuatan Media Pembelajaran Interaktif dengan Power Point di MIS Al Hidayah - Muhammad Syahrizal; Soeb Aripin; Khairunnisa Khairunnisa; Dwina Pri Indini (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The use of learning media is needed by teachers in the teaching process, one of which is easy to use, namely Microsoft Power Point. Power Point software can be used to present learning materials to students to assist teachers in delivering material that is more interesting and easy to understand. Currently, most of Al-Hidayah's MIS teachers do not understand Power Point, so they only use conventional learning media. With the service activities at MIS Al-Hidayah with the theme of using interactive learning media with power points in the new normal era, it is hoped that it can become useful knowledge for teachers to be more creative and innovative in making learning media facilities for the teaching process